Educação e paz em Kant - Gehlen, Maricelia Pereira (My University, 2015)
This present dissertation entitled "Kant on Education and Peace", the result of a master's research of the Graduate Program in Education from Universidade de Caxias do Sul, aims to address the subject education and peace from the pedagogical thinking of philosopher Immanuel Kant. The work part of an analytical and interpretive methodological approach, emphasizing conceptual review, and reflexive and critical reasoning. Inserted in the line of research of philosophy of education, this paper attempts to clarify concepts, and reflect on the contributions present in the pedagogical writings of Kant about education and peace. The works of the philosopher especially considered for the research were: On Pedagogy, Groundwork of the Metaphysics of Morals, To Perpetual Peace and Answer the question: what is enlightenment? Similarly, we intend to update the contributions of the philosopher in order to ascertain their applicability in contemporary educational context through his commentators. Throughout the search, as we looked for arguments to justify and assist the understanding of the traveled path and ideas that based Kantian pedagogy, it was revealed the prominence of his contributions as a theoretical philosopher, and that he is still scarcely studied as theoretical educator. Kant understands education as a process to be developed throughout life, with the goal of forming an autonomous moral subject and, therefore, free. The subject of peace, likewise, should be constituted from such principles, granted from its essence through an elaborate education, that takes it from the minority status and lead it into adulthood, searching for a State equally free, that guarantees it permanent peace. According to Kant the society could not have another constitution but the Republic - for being founded on principles of freedom, dependence on a common law and equality of citizens among themselves. When subject and State are in harmony, where there are no injustices or privileges, it will be likewise unfolding the way for the implementation of what Kant named the United State, and from this, perhaps, to the construction of the Cosmoethical World State.
A presente dissertação, intitulada Educação e Paz em Kant, fruto de uma pesquisa de mestrado, do Programa de Pós - Graduação em Educação, da Universidade de Caxias do Sul, tem por objetivo abordar o tema educação e paz a partir do pensamento pedagógico do filósofo Immanuel Kant. O trabalho parte de uma abordagem metodológica analítica e interpretativa, priorizando a revisão conceitual e a argumentação reflexiva e crítica. Inserido nas pesquisas da filosofia da educação, este trabalho busca esclarecer conceitos, refletir sobre as contribuições presentes nos escritos pedagógicos de Kant a respeito de educação e de paz. As obras do filósofo especialmente consideradas para esta pesquisa foram: Sobre a pedagogia, Fundamentação da Metafísica dos Costumes, À paz perpétua e Resposta à pergunta: que é o iluminismo? Da mesma forma, pretende-se atualizar as contribuições do filósofo no sentido de averiguar sua aplicabilidade no contexto educacional contemporâneo através de seus comentadores. No decorrer da pesquisa, buscando por argumentos que justificassem e auxiliassem o entendimento do trajeto percorrido e por ideias que embasassem a pedagogia kantiana, evidenciou-se o destaque de suas contribuições enquanto teórico da filosofia sendo, ainda, pouco estudado como teórico da educação. Kant entende educação como processo a ser desenvolvido ao longo da vida, tendo como meta a construção do sujeito autônomo e moral, portanto, livre. O sujeito da paz, da mesma forma, deve constituir-se a partir de tais preceitos, garantidos a partir de sua essência por meio de uma educação primorosa que lhe tire do estado menoridade e lhe conduza à maioridade, em busca de um Estado igualmente livre, que lhe garanta a Paz permanentemente. Segundo Kant, a sociedade não poderia ter outra constituição que não fosse republicana - por estar fundada sobre princípios de liberdade, de dependência de uma legislação comum e de igualdade dos cidadãos entre si. Quando sujeito e Estado estiverem em plena harmonia, onde não haja injustiças nem privilégios, estará, da mesma forma, se descortinando o caminho para a implantação do que Kant nominou Estado das Nações. E, a partir deste, quiçá para a construção do Estado Mundial Cosmoético.
Keywords: Educação; Educação - Aspectos sociais; Educação - Filosofia; Paz - Filosofia; Education; Education - Social aspects; Education - Philosophy; Peace - Philosophy